2013
DOI: 10.1016/j.anr.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Turkish Version of the Thirst Distress Scale in Patients on Hemodialysis

Abstract: The psychometric properties of the TDS-T were consistent with those reported in the original study. The TDS-T was found to be a valid and reliable tool for evaluating thirst distress in patients on hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
2
20
1
1
Order By: Relevance
“…1.10) and "Spirituality/religion is a motivator to manage HIV" [22]. On the other hand, a possible explanation regarding the lower mean score in the spirituality/ religion item is that the majority of participants in this study were this study also demonstrated that the factorial structure of the KHSMS was somewhat different compared with the original version used with American women.…”
Section: Discussioncontrasting
confidence: 37%
“…1.10) and "Spirituality/religion is a motivator to manage HIV" [22]. On the other hand, a possible explanation regarding the lower mean score in the spirituality/ religion item is that the majority of participants in this study were this study also demonstrated that the factorial structure of the KHSMS was somewhat different compared with the original version used with American women.…”
Section: Discussioncontrasting
confidence: 37%
“…18 Item 5 remained unchanged in our and other adaptations. 18,19 We added the word "líquido" (liquid) in item 6 and the word "water" was added in a multicenter study. 22 The verb tenses in the other adaptations remained unchanged in the present tense.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated level of internal consistency seen in our adaptation was also observed in other validations of the instrument, with values ranging between 0.78 16 and 0.81. 18 Item 4 had the highest mean score, indicating that having severe dry mouth led to significant distress. This finding was consistent with the mean values reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations